A meta‐synthesis of qualitative studies on stress urinary incontinence in women for the development of a Core Outcome Set: A systematic review. Issue 1 (11th October 2021) - Rada, Maria Patricia; Jones, Stephanie; Betschart, Cornelia; Falconi, Gabriele; Haddad, Jorge Milhem; Doumouchtsis, Stergios K.; ,
Abstract: Objective: Given the high variation of perceptions of women with stress urinary incontinence (SUI), qualitative meta‐synthesis in this field appears warranted. We aimed to synthesize evidence on women's experiences of SUI by analyzing qualitative data. Methods: A literature search of Medline, Embase, Scopus, PsycInfo, and CINAHL databases was performed by a CHORUS Working Group, from inception to August 2020. Qualitative studies on women's perspectives on SUI were included. Thematic analysis was used as a conceptual approach to analyze the data and develop a set of overarching themes. The quality of studies was assessed based on the Critical Appraisal Skills Program tool. Results: Seven studies were included. Six themes encompassing women's perspectives on SUI emerged: experiencing SUI, awareness of SUI, treatments for SUI, sexuality, communication, and psychosocial effects. The quality appraisal of the studies showed good coherence. Conclusion: This study revealed six overarching themes, of which treatment had the highest prevalence. Assessment of women's perceptions of SUI in the context of a qualitative meta‐synthesis may inform policy and practice around this condition, may guide and help set research priorities, and will ideally contribute to the development of a Core Outcome Set for SUI. Abstract : This synthesis may guide SUI‐related research priorities and will contribute to the development of a Core Outcome Set by including patients' perspectives in this process.